FRI0132 Insulin resistance is improved by tocilizumab therapy in rheumatoid arthritis: results from the toward study. (23rd January 2014) - Mirjafari, H.; Wang, J.; Klearman, M.; Harari, O.; Bruce, I.
Abstract : Background: Insulin resistance is increased in rheumatoid arthritis (RA). Reductions in inflammation, glucocorticoid therapy and disease-modifying anti-rheumatic drugs (DMARDs) have been associated with improvement in insulin resistance in patients with RA. Objectives: To study whether tocilizumab (TCZ) therapy, an IL-6 receptor-inhibiting monoclonal antibody, improves insulin resistance in patients with RA. Methods: TOWARD was a phase 3 study in patients with moderate to severe active RA on stable oral DMARDs that compared TCZ 8 mg/kg to placebo with 2:1 randomisation. Insulin resistance was calculated using the homeostatic model (HOMA-IR). Insulin resistance was classified as a HOMA-IR ≥2.2. Associations of baseline HOMA-IR against variables were analysed using linear regression. We examined associations between baseline HOMA-IR and baseline demographics, cardiovascular disease risk factors and disease-related factors using linear regression. Associations between change in HOMA-IR and change in RA disease parameters were also analysed using regression. Results: Of the 1123 patients in the study, HOMA-IR could be calculated in 893 (79.5%). Median (IQR) age, glucose, insulin and HOMA-IR were 54 (46-62) years, 5.1 (4.6-5.6) mmol/l, 7.6 (4.6-12.6) µU/ml and 1.7 (1.0-2.9), respectively. 328 patients (37%) had insulin resistance. In an age- and gender-adjusted analysis, baseline HOMA-IR was associated with older age, higher BMI, SBP and DBP as well as IL-6 level (β-coefficient [95% CI]; 0.01 [0.01, 0.02] per pg/dl), RF positivity (0.25 [0.12, 0.38]) and lower IL-6 receptor levels (–0.02 [–0.02, –0.01] per ng/dl). HOMA-IR was reduced over 24 weeks in patients with insulin resistance who received TCZ but not in those who received placebo (Table ). Image/graph: Conclusions: Insulin resistance is common in RA patients with inadequate response to DMARDs and is associated with RF positivity and IL-6 levels. In patients with pre-existing insulin resistance, HOMA-IR was significantly improved by TCZ therapy while unchanged by placebo. Understanding the mechanistic links between IL-6 and insulin regulation may provide an additional rationale for a stratified approach to using biologics to reduce cardiovascular disease risk in patients with RA. Disclosure of Interest: H. Mirjafari Employee of: Roche Products Ltd, J. Wang Employee of: Roche Products Ltd, M. Klearman Employee of: Genentech, a member of the Roche group, O. Harari Employee of: Roche, I. Bruce Grant/research support from: UCB, Roche, GSK, Genzyme/Sanofi, Consultant for: Pfizer, UCB, GSK, Human Genome Sciences, Roche, Paid instructor for: Pfizer, UCB, GSK, Human Genome Sciences, Roche, Speakers bureau: Pfizer, UCB, GSK, Human Genome Sciences, Roche